Head Teachers’ Instructional Supervision Strategies and Their influence on Effective Implementation Competence Based Education in North Horr Ward, Marsabit County, Kenya - Kalla, Paul Huka; Kanga, Ann; Wambiya, Paschal (Journal of Education and Practice, 2025)
Purpose: This study examined the instructional supervision strategies employed by head teachers and their influence on effective implementation of Competency-Based Education in North Horr Ward, Marsabit County, Kenya—an arid and semi-arid region characterised by limited educational infrastructure and teacher shortages. Methodology: An explanatory sequential mixed methods design was employed, combining a descriptive survey with phenomenological inquiry. Quantitative data were gathered from head teachers and teachers through structured questionnaires, while qualitative insights were obtained via interviews with educational officers, focus group discussions with pupils, and document analysis. Findings: The findings revealed that while head teachers frequently engaged in classroom visits, collaborative planning, and review of professional documents, practices such as providing feedback, supporting continuous professional development, and recognising exemplary performance were inconsistently executed. Challenges identified included teacher resistance, heavy workload, lack of supervisory skills, inadequate resources, and limited support from education officials due to logistical constraints. Unique Contribution to Theory, Policy and Practice: The study recommends targeted capacity building for head teachers, increased staffing, improved logistical support for supervisory officers, and the institutionalisation of professional development and feedback mechanisms to enhance curriculum delivery and teacher support in remote areas.